Optimization of Cassava-Based Non Rice Food Development Using Funds Stimulation of Qardhul-Hasan Transactions - Machfudz, Masyhuri (MEC-J (Management and Economics Journal), 2020)
This research activity was done holistically from beginning to end, starting from 3rdLevel of Readiness Technology (TKT + 3) to downstream dominance level. The research objective was to optimize the implementation of Social Engineering Copyright (RS-JGTS) and implementation of TTG-Ts+ in order to realize an independent and sustainable cassava-based food fulfilment center. It used Participatory Action Research (PAR) method to facilitate and motivate the community (producer farmers) to create self-sufficiency food. The strategy to conduct action research was based on O'Brien (2002). The supporting facilities for nutritional analysis in TS + morphology were from the laboratory of life sciences center (LSIH) and simulation analysis. The research results showed that upstream aspects:the implementationof Social Engineering Copyright Cassava Planting Movement Group-(JGTS) in sustainable cassava farming business as a mediumto develop sustainability of cassava raw materials was done with qardhul-hasan transactions facility for costs production through partnership with producers farmers through stimulant fund of qardhul-hasan for production cost with share instalment was done through agreement of cassava; downstream aspect; the implementation of copyright appropriate technology for cassava flour PLUS (TTG Ts +), to realize processed products of dry cassava, cassava flour and mocaf flour. The next was the agreement of cassava-based fast food creation for cassava noodles, onde-onde, and others. The technological readiness (TKT) was at 3-4 level, therefore it need further research in order to increase TKT at a higher level to becomes more optimal.